2020
DOI: 10.3390/sports8120163
|View full text |Cite
|
Sign up to set email alerts
|

Supra-Versus Submaximal Cycle Ergometer Verification of VO2max in Males and Females

Abstract: This study was designed to determine the optimal intensity for verification phase testing (VP) in healthy, young adults. Thirty one young, active participants (16 females) completed a cycle ergometer graded exercise test (GXT) VO2max test and 4 VP tests at 80, 90, 100, and 105% of the maximum wattage achieved during the GXT. GXT and VP VO2max values showed a significant test x sex interaction (p = 0.02). The males elicited significantly higher VO2max values during the GXT, 80%, and 90% when compared to the 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 40 publications
6
11
1
Order By: Relevance
“…However, there was no sig-nificant difference in squatting and VO 2 max between the two genders (p > 0.05). This is different from the results of previous studies [42][43][44]. We concluded the following two possible reasons: first, the number of subjects in this test was small and covered a smaller range of oxygen uptake; second, the heart rate was not observed during squatting exercise, so it could not be determined whether the subjects reached exhaustion.…”
Section: Discussioncontrasting
confidence: 80%
“…However, there was no sig-nificant difference in squatting and VO 2 max between the two genders (p > 0.05). This is different from the results of previous studies [42][43][44]. We concluded the following two possible reasons: first, the number of subjects in this test was small and covered a smaller range of oxygen uptake; second, the heart rate was not observed during squatting exercise, so it could not be determined whether the subjects reached exhaustion.…”
Section: Discussioncontrasting
confidence: 80%
“…In our own studies, the warm-up lasted 15 min, including 5 min of VT1 effort and 10 min of effort measured halfway between VT1 and VT2. We concluded that such a warm-up, performed before the verification test on a separate day, may allow to obtain higher VO 2peak values than in the above-cited works (Scharhag-Rosenberger et al, 2011;Possamai et al, 2020;Sawyer et al, 2020). This assumption was supported by the results of our own previous studies (Hebisz et al, 2017), in which we also used a long warm-up time.…”
Section: Discussionsupporting
confidence: 72%
“…Schaun (2017) also stated that the time elapsed between an incremental test and a verification test is not a key aspect to achieving the verification criterion. Attempts were also made to perform tests to verify VO2max on a different day than the progressive test (Scharhag-Rosenberger et al, 2011;Possamai et al, 2020;Sawyer et al, 2020). Possamai et al (2020) found that during the verification test performed on a separate day, the exercise capacity is greater than during the verification test performed several minutes after the progressive test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations